Radiative heat load distribution on the EU-DEMO first wall due to mitigated disruptions. (December 2020) - Moscheni, M.; Carr, M.; Dulla, S.; Maviglia, F.; Meakins, A.; Nallo, G.F.; Subba, F.; Zanino, R.
Highlights: CHERAB code to compute radiative loads on EU-DEMO PFCs due to mitigated disruption. A procedure to improve the Monte Carlo statistics in the CHERAB code is presented. Computed peak heat flux due to mitigated disruption: 488 M W / m 2 on upper limiter. Abstract: The EU-DEMO First Wall (FW) will be a relatively thin structure. In order not to damage this layer, heat loads distributed onto the wall should be carefully controlled. In the case of transient events, as for example plasma disruptions, the steady-state heat load limit ( ∼ 1 - 2 M W / m 2 ) can be largely exceeded for a timespan sufficiently long to cause damages. Therefore, when the control system detects an upcoming disruption, Shattered Pellet Injection (SPI) or Massive Gas Injection (MGI) mitigation techniques can be employed to inject impurities and switch off the plasma safely. In the present work, the Monte-Carlo ray-tracing code CHERAB is used to compute the radiative heat load distribution on the EU-DEMO Plasma Facing Components (PFCs) due to a mitigated plasma disruption. By applying ad-hoc techniques to improve the quality of the Monte Carlo calculation, we obtain a peak radiative load of ∼ 490 M W / m 2 on the PFCs, which is ∼ 25 % lower than previous estimates.